PENGEMBANGAN MEDIA KARTU TRUTH OR DARE UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SD NEGERI KOWANGBINANGUN SLEMAN - Nurrahman, Irfan; Beny Dwi Lukitoaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to explore the applicability and utility of truth or dare card media as an educational medium to strengthen concept mastery among Grade V students in the Pancasila subject at Kowangbinangun State Elementary School. The study is categorized as Research and Development. All 18 students participated as subjects through the use of complete enumeration sampling. The data collection process was conducted through observation, interviews, tests, and questionnaires. Instrument validity was evaluated through expert judgment (judge experts), while instrument reliability was assessed using interview sheets, observation forms, and both pre-test and post-test sheets. Data analysis was carried out using a quantitative approach. The findings reveal that the appropriateness of the truth or dare card media as a learning tool to enhance students’ conceptual understanding in Pancasila education for fifth-grade students at Kowangbinangun State Elementary School was appraised by media experts with an average validation score of 4.5, and by material experts with an average score of 4, thus declaring the media feasible for improving students' comprehension and suitable for implementation. Moreover, the truth or dare card media proved to be a usable instructional tool to help enhance the conceptual grasp of Pancasila education among fifth-grade learners at Kowangbinangun State Elementary School. This conclusion is drawn from teacher assessments, which yielded an average of 4.6, and student evaluations, which showed a mean score of 4.67. Accordingly, the media can be regarded as efficient in practice.